2018
DOI: 10.1002/ejp.1194
|View full text |Cite
|
Sign up to set email alerts
|

Dipyrone is the preferred nonopioid analgesic for the treatment of acute and chronic pain. A survey of clinical practice in German‐speaking countries

Abstract: A survey of anaesthesiologist in German-speaking countries revealed dipyrone as preferred nonopioid analgesic for the treatment of acute and chronic pain. Benefits seem to outweigh the risks, specifically the risk of agranulocytosis. Information of medical staff and patients on adverse drug reactions and symptoms of agranulocytosis should be implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
21

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 48 publications
0
15
0
21
Order By: Relevance
“…Dipyrone was removed from the market in India in 2013, only to be re‐introduced in 2014 subject to specific warning and indications. A 2016 survey of anaesthesiologists in German‐speaking countries reported that dipyrone is the preferred nonopioid analgesic for the treatment of acute and chronic pain …”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Dipyrone was removed from the market in India in 2013, only to be re‐introduced in 2014 subject to specific warning and indications. A 2016 survey of anaesthesiologists in German‐speaking countries reported that dipyrone is the preferred nonopioid analgesic for the treatment of acute and chronic pain …”
Section: Commentmentioning
confidence: 99%
“…A 2016 survey of anaesthesiologists in German-speaking countries reported that dipyrone is the preferred nonopioid analgesic for the treatment of acute and chronic pain. 27 Interethnic differences in drug response are well known, and therefore, regulatory authorities require subset analysis of safety and efficacy data by demographic variables such as age, gender and ethnicity/race. 28 for use in the treatment of heart failure as an adjunct to standard therapy in self-identified Black patients.…”
Section: Commentmentioning
confidence: 99%
“…So kam es 2016 im Vergleich zu 2011 bereits zu einer Zunahme der Verordnung von Metamizol um 9 % [11]. Gerade bei perioperativer Analgesie und chronischen Schmerzen ist es das beliebteste Nicht-Opioid-Analgetikum im deutschsprachigen Raum [12]. Dies ist wohl darauf zurückzuführen, dass viele der verordnenden Ärzte Metamizol aufgrund der guten analgetischen Wirkung bei geringerer Nebenwirkungsrate im Vergleich zu nichtsteroidalen Antirheumatika für das Nicht-Opioid-Analgetikum mit dem besten Risiko-Nutzen-Verhältnis halten [13,14].…”
Section: Introductionunclassified
“…29,30 In these countries, the drug is still commonly used for indications such as cancer pain, colic pain, postoperative pain, headache, or pain resulting from acute injuries, among others. 3,6,[32][33][34][35] For instance, metamizole was the third most prescribed analgesic drug in Switzerland in the period between 2006 and 2013, and in Germany it was the most prescribed analgesic substance in 2012, with more than 140 million defined daily doses. 28,36 In countries where metamizole is sold over the counter, the drug is used as a common self-medication and is the most taken analgesic agent in patients with chronic pain.…”
mentioning
confidence: 99%